Pengaruh Penggunaan Aplikasi Otentikasi dan Benefits Offered Terhadap Kepuasan Nasabah dalam Bertransaksi pada PT Taspen Persero Cabang Gorontalo - Nurain Putri Wahab; Raflin Hinelo; Yulinda L.Ismail (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to. Analyze and find out how the use of authentication applications and benefits offered affect customer satisfaction. The population consists of 63,569 active pensioners at PT Taspen Persero Gorontalo Branch from 2019-2023, and the sample is 100 pensioners obtained using a purposive sampling technique. The analysis is done using a quantitative method using multiple linear regression analysis. According to the result, it shows that (1) the authentication application variable partially contributed a positive and significant effect on customer satisfaction with a significance level of 0.000 <0.05 and the value of table count, with the result of 2.727> 1.660. (2) the Benefits Offered variable partially contributed a positive and significant effect on customer satisfaction with a significance level of 0.008 <0.05 and the value of stable> count, with the result of 4.010 > 1,660. (3) it was simultaneously concluded that there was a positive and significant influence between the authentication application variable and the Benefits Offered variable on Customer Satisfaction with a significance level of 0.000 <0.05 and a value of Fiable Fcount, or18.328 3.09. The R square determination coefficient was 0.574, which means that the influence contribution percentage of the authentication application and Benefits Offered affects customer satisfaction by 57.4%. In other words, the correlation level of the R square value was sufficient, and the other 42.6% came from other variables that were not examined.